Determining the optimal contrast-enhanced voiding urosonography technique for vesicoureteral reflux in children and adolescents: a systematic review and network meta-analysis - Hu, Sha; Tian, Yu; He, Min (Frontiers in Pediatrics, 2025)
AimTo evaluate diagnostic combinations of imaging modalities and contrast agents for vesicoureteral reflux (VUR) in children.MethodsStudies were retrieved in PubMed, EMBASE, Cochrane Library, Web of science, and China National Knowledge Infrastructure (CNKI) until March 16, 2023. We used bivariate random-effects model and a frequentist model for meta-analysis. Surface under the cumulative ranking curve (SUCRA) was used to rank ceVUS protocols.Results19 studies identified 4 diagnostic combinations. Contrast-harmonic ultrasound with SonoVue® (CHSV) had significantly lower sensitivity, specificity, and diagnostic accuracy than VCUG, although its negative predictive value was higher than VCUG. Contrast-harmonic ultrasound with Optison™ (CHOS) was comparable to VCUG across all diagnostic measures. SUCRA analysis favored CHOS, with probabilities of being the best for SEN, SPE, PPV, NPV, DOR, and DA at 50.9%, 16.6%, 42.6%, 57.4%, 36.2%, and 20.4%, respectively.ConclusionHarmonic VUS with Optison™ may be the optimal protocol for VUR detection in children.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023424510, identifier (CRD42023424510).